The role of works councils for severance payments - Christian Grund; Johannes Martin (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Using representative German employee data, we analyse the role of works councils for the incidence of severance payments subsequent to dismissals. While there is a positive relation with severance payments after those dismissals which stem from plant closings, the incidence of a works council is negatively associated with severance pay subsequent to individual layoffs. In both cases, we find a negative moderating effect of individuals' higher re-employment chances. We also explore gender differences and differences between the types of previously held jobs.
Keywords: J53; J63; J65; 330; Dismissals; Layoffs; Plant closings; Severance pay; Works councils